2006
DOI: 10.2134/jeq2005.0410
|View full text |Cite
|
Sign up to set email alerts
|

Use of Beryllium‐7 to Document Soil Redistribution following Forest Harvest Operations

Abstract: Rapid and reliable methods for documenting soil erosion associated with forest harvest operations are needed to support the development of best management practices for soil and water conservation. To address this need, the potential for using 7Be measurements to estimate patterns and amounts of soil redistribution associated with individual post-harvest events was explored. The 7Be technique, which was originally developed for use on agricultural land, was employed to estimate soil redistribution associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 27 publications
1
43
0
5
Order By: Relevance
“…It has been used to measure flood deposits on the inner shelf (e.g., Sommerfield et al, 1999), soil redistribution following catchment erosion (e.g., Schuller et al, 2006), and to track monsoon-derived sediment deposition on the abandoned Bengal tidal delta plain (e.g., Rogers et al, 2013). We set 0.2 dpm g -1 as the limit for detectable 7 Be to account for minor atmospheric contributions directly to the fluvial-tidal delta plain.…”
Section: Beryllium-7 Geochemistrymentioning
confidence: 99%
“…It has been used to measure flood deposits on the inner shelf (e.g., Sommerfield et al, 1999), soil redistribution following catchment erosion (e.g., Schuller et al, 2006), and to track monsoon-derived sediment deposition on the abandoned Bengal tidal delta plain (e.g., Rogers et al, 2013). We set 0.2 dpm g -1 as the limit for detectable 7 Be to account for minor atmospheric contributions directly to the fluvial-tidal delta plain.…”
Section: Beryllium-7 Geochemistrymentioning
confidence: 99%
“…Field and laboratory experiments performed since the early 1990s indicate that 7 Be in bare soils as well as in soils covered with vegetation often shows an approximately exponential decrease with depth, with most of the activity found within the upper few millimetres of the soil surface (Walling & Woodward 1992;Wallbrink & Murray 1996;Walling et al 1999;Schuller et al 2006Schuller et al , 2008. An exponential decline of 7 Be with depth indicates equilibrium between deposition and decay.…”
mentioning
confidence: 99%
“…Figure 2 presented the characteristic soil depth profile of beryllium-7 for the analyzed soil type of the studied areas, which showed exponential decay in soil depth, as presented in the literature (Matissoff et al, 2002;Schuller et al, 2006). Figure 2 showed that the beryllium-7 deposited in the soil was whole adsorbed in the first 2 cm of soil, independent of the pluviometric precipitation.…”
Section: Methodsmentioning
confidence: 68%
“…Some works have demonstrated the potential for using beryllium-7 in tracing of sediment in marine and lacustrine systems and how beryllium-7 could be used to fingerprint sediment derived from superficial sources (Wan et al, 1987;Wallbrink and Murray, 1996;Blake et al, 1999). In South America, only one work carried out in Chile has applied beryllium-7 to study the soil redistribution (Schuller et al, 2006). Schuller et al (2006) employed beryllium-7 to estimate the soil redistribution associated with a period of heavy rainfall within a harvested forest area and showed the applicability of beryllium-7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation